Europe's sea mammals : including the Azores, Madeira, the Canary Islands and Cape Verde : a field guide to the whales, dolphins, porpoises and seals - Still, Rob; Harrop, Hugh; Stenton, Tim; Días, Luis (WildGuides., 2019)
A state-of-the-art photographic identification guide to Europe's whales, dolphins, porpoises and sealsThis cutting-edge photographic identification guide to Europe's sea mammals--the only such guide of its kind--covers the 39 species of whales, dolphins and porpoises and 9 species of seals found in the region, which spans the eastern Atlantic from Iceland to Macaronesia, and the Mediterranean, Caspian and Baltic seas. Written and illustrated by a team of professional tour guides with extensive experience presenting the region's sea mammals, the guide features more than 180 color photographs, maps and graphics, highlights key identification features and includes information on the range, ecology, behaviour and conservation status of each species. Produced with the marine conservation charity ORCA, the book presents mapping data from a decade of surveys, which shows both current distribution and changes over time. Europe's Sea Mammals is an essential companion for whale watchers and anyone else who is interested in this enigmatic group of mammals. The only photographic guide dedicated to this popular whale-watching regionFeatures more than 180 color photos, maps and graphicsHighlights key identification features and provides essential information on the range, ecology, behaviour and conservation status of each species.